Biological treatment of POME (high acidic content) factorial analysis - Nuratiqah, Marsidi (2013)
Palm Oil Mill Effluent(POME)is an effluent discharged from unrecovered palm oil extraction process and typically acidic (pH 4 to 5.5).Disposing POME without treatment would give adverse effect to environment as well as human being. Therefore,biological treatment using various microbes is suitable to employ to increase the pH of POME since it is low cost and safe.The aim of this study was to study the factors which are influencing the biological pH treatment of acidic POME.The factors involved in this study are agitation speed,temperature,reaction time,inoculum to POME ratio and light intensity.To begin, sample of acidic POME was collected from a nearby palm oil mill in Gambang, Pahang while soil mixed culture was obtained from soil near to plants root system.Preliminary study on reaction time and potential microbes was done in 10 days and at the end,soil mixed culture performed better utilization process than Enterobacter sp. with pH 5.58.Then, an acclimatization of soil mixed culture was conducted and 32 experimental runs were done according to two level factorial.An analysis using Design Expert Software shows that three factors are contribute in increasing the value of pH which is agitation speed, temperature and reaction time with 19.08%, 7.58% and 4.68% respectively.Interaction between factor temperature and agitation speed gives highest percentage of contribution with 17.30% in existence of interaction, followed by interaction of factor temperature and inoculum to POME ratio and interaction of factor reaction time and agitation speed with 8.41% and 7.03% respectively.It is predicted the best conditions regarding this study for agitation speed, temperature, reaction time, inoculum to POME ratio and light intensity lies on the value of 138.89 rpm, 28.98 ºC, 8.81 days,ratio 1:3 and with light respectively. All the best conditions provided a stable pH value which is 6.9999. Overall, factors of agitation speed, temperature and reaction time are suitable to be the factors for optimization experiment.